The effects of coating materials in spark ignition engine design - Durat, Mesut; Kapsiz, Murat; Nart, Ergun; Ficici, Ferit; Parlak, Adnan (ELSEVIER SCI LTD, 2012)
Ceramic coatings provide good thermal barrier properties for designers. In the design of adiabatic engines, reducing in-cylinder heat rejection requires very special thermal barrier coatings on the engine combustion chamber. Partially, thermal barrier coating (TBC) on the top surface of the piston in the annulus form is considered as a solution for unburned HC emission produced by incomplete combustion with respect to crevice volume after SI engines start (the three-way catalytic converter is not yet activated in the period of first 120 s). Because TBC on the top piston surface decreases the thermal conductivity and increases the unburned charge oxidation by increasing the temperature in the flame quenching area near the entrance of the crevice volume between the piston and liner during the compression and the early part of the expansion strokes. In this study, a steady-state thermal analysis was performed to evaluate the temperature gradients in the standard and two different partially stabilized ceramic coated pistons by using Abaqus (c) finite element (FE) software. A sharp increase in the temperature of the coated area of the piston was observed as a result of FE simulations. It is concluded that the annulus Y-PSZ coating may contribute better, as compared to Mg-PSZ, to decrease the cold start and steady state HC emissions without auto ignition, since the temperature in the area shows a local sharp increase. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: THERMAL BARRIER COATINGS; DIESEL-ENGINE; EXHAUST-GAS; PERFORMANCE; TRANSFORMATION; EMISSIONS; EXERGY; Materials Science